2002
DOI: 10.1002/jmv.10188
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of pre‐S/surface and pre‐core/core promoter genes of hepatitis B virus in chronic hepatitis C patients with occult HBV infection

Abstract: Although occult hepatitis B virus (HBV) infection in individuals without detectable hepatitis B surface antigen (HBsAg) may occur and has been reported to be common in patients with chronic hepatitis C, the related molecular mechanisms remain unknown. With the polymerase chain reaction, serum HBV DNA was sought in 100 HBsAg-negative patients with chronic hepatitis C virus (HCV)-infection. In those with occult HBV infection, possible genomic variability of HBV was evaluated by amplification and direct sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 25 publications
(28 reference statements)
2
38
1
Order By: Relevance
“…[33][34][35] In addition, A1762T/G1764A was observed in only one child, who had recovered from wildtype HBV infection. Although previous studies have reported A1762T/G1764A mutations in occult HBV infection, [11][12][13] the correlation between these mutations and occult HBV infection remains unclear. No other mutations were found in the core region in this study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…[33][34][35] In addition, A1762T/G1764A was observed in only one child, who had recovered from wildtype HBV infection. Although previous studies have reported A1762T/G1764A mutations in occult HBV infection, [11][12][13] the correlation between these mutations and occult HBV infection remains unclear. No other mutations were found in the core region in this study.…”
Section: Discussionmentioning
confidence: 94%
“…10,11 Moreover, previous studies have suggested that variations in the core region may be responsible for the lack of HBsAg. 12,13 The status of HBV is of particular concern in Indonesia, an area with intermediate-to-high endemicity for HBV infection and a carrier rate of 5-20% in the general population. 5 Most chronic HBV carriers were infected in early infancy.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of G145R mutant in the PBL may be associated with immunosilent carriage (HBsAg and anti-HBc negative, Chakravarty et al, 2000;Kao et al, 2002). Alternatively, immunosilent HBV infection may be observed in HBV carriers of double mutants with amino acid substitutions in the "a" determinant of the S antigen as well as in the C gene leading to truncated HBeAg and core proteins (Schories et al, 2000).…”
Section: Hbv Mutants and Diagnostic Assaysmentioning
confidence: 91%
“…Datta et al [26] reported that about half of the subjects with occult HBV infection had no substitutions in the major hydrophilic loop region. It was suggested that besides the major hydrophilic loop region of the S gene, substitutions or deletions in the pre-S gene [27] , core promoter gene [28] or reverse transcriptase domain in the pol gene [29] can affect the synthesis of viral envelope protein or suppress the replication of HBV DNA, thus result in the absence of circulating HBsAg. However, the results from previous studies are still not consistent and need further investigations.…”
Section: Discussionmentioning
confidence: 99%